2016
DOI: 10.4999/uhod.161104
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic and Proapoptotic Activities of Anatolian Macrovipera Lebetina Obtusa (Dwigubski, 1832) Crude Venom on Cultured K562 Human Chronic Myelogenous Leukemia Cells.

Abstract: In the context of searching for anticancer compounds in natural products, snake venom is one of the important sources for peptide/ protein based bioactive molecules. Proteins and peptides with anticancer activity were purified and identified from snake venoms. The aim of the present study was to determine the in vitro cytotoxicity of Macrovipera lebetina obtusa (Blunt-Nosed Viper) crude venom from southeastern Anatolia against K562 human chronic myelogenous leukemia (CML) cells by 3-(4,5-dimethylthiazol-2-yl)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…Crude venom of M. l. obtusa showed dose-dependent cytotoxicity against some cancer cell lines, kidney epithelial cells from African green monkey (Vero), and human embriyonic kidney 293 cells (HEK-293) in previous studies (Samel, Trummal, Siigur, & Siigur, 2012;Ozen, İğci, Yalçin, Goçmen, & Nalbantsoy, 2015;Jahromi, Mirakabadi, & Kamalzadeh, 2016;Süzergöz et al 2016;Oghalaie, Kazemi-Lomedasht, Zareinejad, & Shahbazzadeh, 2017). Moreover, dose-dependent cytotoxic activity of M. l. lebetina venom against L929 mouse fibroblast cell line was also reported previously (Nalbantsoy et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
“…Crude venom of M. l. obtusa showed dose-dependent cytotoxicity against some cancer cell lines, kidney epithelial cells from African green monkey (Vero), and human embriyonic kidney 293 cells (HEK-293) in previous studies (Samel, Trummal, Siigur, & Siigur, 2012;Ozen, İğci, Yalçin, Goçmen, & Nalbantsoy, 2015;Jahromi, Mirakabadi, & Kamalzadeh, 2016;Süzergöz et al 2016;Oghalaie, Kazemi-Lomedasht, Zareinejad, & Shahbazzadeh, 2017). Moreover, dose-dependent cytotoxic activity of M. l. lebetina venom against L929 mouse fibroblast cell line was also reported previously (Nalbantsoy et al, 2012).…”
Section: Discussionsupporting
confidence: 60%
“…The protein profile of M. lebetinus venom as obtained by 2D-PAGE in the present study is consistent with a previous study by Igci and Demiralp [8]. Earlier studies have shown that the most abundant proteins classes found in M. lebetinus venom are SVMP, SVSP, PLA 2 , CLP, LAAO, and disintegrin [8,[22][23][24], which are responsible for Its pathogenesis and biological activities [9][10][11][12].…”
Section: Discussionsupporting
confidence: 91%
“…The following protein families have been identified in the venom of M. lebetinus up to date: snake venom metalloproteinase (SVMP), snake venom serine proteinase (SVSP), phospholipase A 2 (PLA 2 ), ʟ-amino acid oxidase (LAAO), hyaluronidase, 5´-nucleotidase, phosphodiesterase (PDE), C-type lectin-like protein (CLP), cysteine-rich secretory protein (CRISP), vascular endothelial growth factor (VEGF), nerve growth factor (NGF), disintegrin, Kunitz-type serine protease inhibitor, bradykinin-potentiating peptide (BPP), and natriuretic peptide [7,8]. These proteins are responsible for the biological activities of M. lebetinus venom such as cytotoxic, antimicrobial, antiaggregant, anticancer, anti/procoagulant, necrotic and hemorrhagic activities [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…via blockage of integrins, induction of apoptosis or necrosis pathways and disruption of the cell cycle (Calderon et al, 2014;Göçmen et al, 2015a;Sciani and Pimenta, 2017;Yalcın et al, 2014;Zainal Abidin et al, 2018). This correlates to some extent with chemotherapeutic agents that are currently being used in clinics, making venoms attractive sources of future anti-cancer agents (Calderon et al, 2014;Meyer et al, 2004;Nalbantsoy et al, 2017;Suzergoz et al, 2016).…”
Section: Introductionmentioning
confidence: 99%